2021
DOI: 10.3390/ma14185462
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy as a Novel Method for the Characterization of Polydioxanone Medical Stents Biodegradation

Abstract: Polydioxanone (PPDX), as an FDA approved polymer in tissue engineering, is an important component of some promising medical devices, e.g., biodegradable stents. The hydrolytic degradation of polydioxanone stents plays a key role in the safety and efficacy of treatment. A new fast and convenient method to quantitatively evaluate the hydrolytic degradation of PPDX stent material was developed. PPDX esophageal stents were degraded in phosphate-buffered saline for 24 weeks. For the first time, the changes in Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 49 publications
7
10
0
Order By: Relevance
“…The results are summarized in Table 2 . The crystallinity increases with the degradation period, which is in good agreement with previously published works [ 56 , 61 , 62 , 63 ]. In the beginning, the increase in the proportion of the crystalline phase was small (around 2%).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The results are summarized in Table 2 . The crystallinity increases with the degradation period, which is in good agreement with previously published works [ 56 , 61 , 62 , 63 ]. In the beginning, the increase in the proportion of the crystalline phase was small (around 2%).…”
Section: Resultssupporting
confidence: 92%
“…No crazes or cracks were observed even after this degradation period. It is not very surprising, as in the observation reported by Loskot, et al [ 56 ], esophageal PPDX stents after 8 weeks of degradation in PBS only rarely showed tiny crazes. This slight discrepancy in the surface deterioration speed can be explained by the fact that different types of stents were analyzed in these studies.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations